Preexposure prophylaxis-related stigma: strategies to improve uptake and adherence – a narrative review - Haire BG (Dove Medical Press, 2015)
Bridget G Haire Kirby Institute for Infection and Immunity in Society, University of New South Wales, Sydney, NSW, Australia Abstract: Despite high levels of efficacy, the implementation of preexposure prophylaxis (PrEP) as a strategy to prevent new HIV infection has been slow. Studies show that PrEP works so long as it is taken, making adherence one of the great challenges of effective PrEP implementation alongside issues of access and uptake. Given that effective PrEP use requires ongoing self-administration of pills by people at high risk of HIV acquisition, it is a strategy best understood not as simply biomedical, but as biobehavioral or biopsychosocial, meaning that that social, psychological, cultural, and structural factors all contribute to the success or failure of the intervention. The willingness of people at risk of HIV to take up and adhere to PrEP depends greatly upon social understandings – whether it is seen as effective, as a healthy option, and a socially acceptable strategy for preventing HIV. Stigma – unfavorable associations – can negatively influence the implementation of PrEP. Because it is associated with high-risk sexual activity, PrEP risks multiple stigmas that can differ according to specific cultural conditions. This includes the stigma of being related to HIV (which may also relate to other stigmas, such as homosexuality, sex work, and/or drug use) and the stigma of PrEP being an alternative to condoms (as condom use is associated with responsible sexual activity). PrEP-related stigma has emerged as a significant social harm that can arise from PrEP research participation, reported by trial participants from a range of different trial sites, different trial populations, and spanning different continents. Social marketing needs to redress PrEP-related stigmas through health promotion campaigns aimed at clinicians, HIV-affected communities, and people at high risk of HIV who might benefit from PrEP access. PrEP access needs to be reframed as a positive and responsible option to help people remain HIV-negative. Keywords: HIV prevention, discrimination, PrEP